FMCW Radar Phase-Processing for Automotive Application - Karlisa Priandana; Alex Coccia; Leo P. Ligthart (Institut Teknologi Sepuluh Nopember, 2014)
An unmanned high-speed vehicle requires a high resolution control unit to decide whether the vehicle should break or steer. This paper describes the utilization of a Frequency Modulated Continous Wave (FMCW) radar to detect the distance and angular position of the target relative to the moving vehicle. These informations are calculated from some numbers of data obtained from a radar system that is mounted on the moving vehicle. To obtain a high angular resolution, a phase-processing approach is introduced by extracting the constant phase information from the radar FMCW beat signal. It is found that a very high angular resolution can be obtained by processing the phase information, independent from the change of relative velocity between the radar and the target. However, this method requires a very stable radar system with high phase resolution and accuracy.